Septic femoral and caval thrombophlebitis secondary to acute appendicitis: A case report - Daniel B. Gehle; Philip W. Morgan; Sara A. Mansfield; Regan F. Williams; Howard I. Pryor, II (Elsevier, 2024)
Introduction: Septic thrombophlebitis (STP) of deep veins is a rare condition that harbors significant morbidity in the pediatric population. Most cases of STP in pediatric patients have been associated with head and neck infections such as in Lemierre syndrome. Case presentation: A 3-year-old male presented with a 10-day history of fever, abdominal pain, and diarrhea and was diagnosed with perforated appendicitis. He underwent laparoscopic hand-assisted appendectomy and was discharged on post-operative day 5. He re-presented to the emergency department two weeks later with several day history of abdominal distension and vomiting and imaging demonstrated a high-grade small bowel obstruction. He underwent exploratory laparotomy and ileocecectomy. His postoperative course was complicated by acute respiratory failure secondary to abdominal compartment syndrome requiring decompressive laparotomy. His clinical status improved and he was able to undergo abdominal closure 4 days later. He then developed persistent fevers and was found to have deep venous thrombosis of bilateral femoral veins extending to the infrarenal inferior vena cava consistent with septic thrombophlebitis. He was successfully treated for his deep venous thrombosis with a course of antibiotics and therapeutic anticoagulation and has made a full recovery. Conclusion: STP of deep veins is generally managed with antibiotics and therapeutic anticoagulation and rarely requires invasive interventions. This case highlights that in young children, the inferior vena cava is small enough caliber to develop thrombosis and that STP of the pelvic veins and inferior vena cava can occur secondary to intraabdominal infection and its sequelae.